Fragilidade como preditora a desfechos adversos de saúde em idosos usuários da Atenção Primária : estudo de coorte - Lopes, Edilene Gianelli (2019)
Population aging brings concerns related to chronic and multiple health conditions, being a concrete and gradual situation. The fragility, multidimensional, is an essential marker for the detection of risks related to the health of the elderly. It is understood as a predictive factor for such disorders that reflect in greater number of functional disabilities, institutionalization with the recurrent use of specialized services, falls and premature death. OBJECTIVE: To analyze the effect of fragility as a predictor variable for adverse health outcomes in the elderly followed up by Primary Health Care. METHODS: Epidemiological study of a fixed cohort in a 24 - month follow - up with 377 elderly individuals, aged 60 years and over, living in Várzea Grande - MT. This work used for the baseline the Tilburg Frailty Indicator (TFI) guiding instrument recently validated in Brazil by the ENSP / Fiocruz Research Group. The research was submitted and approved by the Research Ethics Committee under the number of opinion 2,771,193 and CAAE 89020318.6.0000.5166. RESULTS: The prevalence of fragility at the baseline was 65.25%. The incidence of adverse health outcomes in frail elderly individuals for loss of functional capacity in ADL was 25.25%; hospitalization was 31.31% and; 41.41% fell. In the Incidence Ratio (RR), only the outcome remained associated with frailty, since among fragile elderly patients, the risk of falls increased by 57% compared to non- fragile elderly patients with p value of 0.040 (IC 95% 1.02-2.41). CONCLUSION: The study pointed to a high incidence of adverse health outcomes, emphasizing the importance of longitudinal studies that estimate the causality of these events in order to stimulate preventive actions that minimize functional disability and premature death. It was contacted that TFI is a good predictor of adverse health events in the elderly population to be used in follow-up by Brazilian primary care.